Use of automated technology and its impact on productivity ciprofloxacin 500 mg coated tablets - Pérez, Frank A. (2017)
In this research was evaluated the impact of use of automated technology in unit operations and manufacturing productivity of ciprofloxacin 500 mg coated tablets, kneading and drying stages of granulated were moved to automated equipment, identifying critical parameters of new process; also were quantified and compared the man/hours used in new process. The process was carried out through two stages: kneading in High Shear mixer granulator and drying in fluid bed dryer. The physical, chemical and microbiological product results obtained by new design were in accordance with previously established quality specifications for this product, as 98,67% dissolution and compliance of accelerated stability studies. Were concluded that the use of automated technology under the proposed design was satisfactory, quality attributes were improved and reported a 50% saving in time about man/hours and machine/hours.